Question
upstudy study bank question image url

For the functions \( f(x)=\frac{5}{x+2} \) and \( g(x)=\frac{1}{x-2} \), find the composition \( f \circ g \) and simplify your notation. \( \begin{array}{l}(f \circ g)(x)=\square \\ \text { Domain of } f \circ g: \square\end{array} \)

Ask by Mccarthy Horton. in the United States
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (f \circ g)(x) = \frac{5(x-2)}{2x-3} \) Domain of \( f \circ g \): \( x \neq \frac{3}{2} \)

Solution

To find the composition \( f \circ g \) of the functions \( f(x) = \frac{5}{x+2} \) and \( g(x) = \frac{1}{x-2} \), we need to substitute the expression for \( g(x) \) into \( f(x) \) and simplify the resulting expression. Given: \( f(x) = \frac{5}{x+2} \) \( g(x) = \frac{1}{x-2} \) Substitute \( g(x) \) into \( f(x) \): \( (f \circ g)(x) = f(g(x)) = \frac{5}{g(x)+2} \) Substitute \( g(x) = \frac{1}{x-2} \) into the expression: \( (f \circ g)(x) = \frac{5}{\frac{1}{x-2}+2} \) Simplify the expression: \( (f \circ g)(x) = \frac{5}{\frac{1}{x-2}+2} = \frac{5}{\frac{1+2(x-2)}{x-2}} = \frac{5}{\frac{1+2x-4}{x-2}} = \frac{5}{\frac{2x-3}{x-2}} = \frac{5(x-2)}{2x-3} \) Therefore, the composition \( f \circ g \) is \( \frac{5(x-2)}{2x-3} \). To find the domain of \( f \circ g \), we need to ensure that the denominator of the composition is not equal to zero. The denominator is \( 2x-3 \), so the domain of \( f \circ g \) is all real numbers except when \( 2x-3 = 0 \), which gives \( x = \frac{3}{2} \). Therefore, the domain of \( f \circ g \) is \( x \neq \frac{3}{2} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the composition \( f \circ g \), we need to substitute \( g(x) \) into \( f(x) \). First, we have: \[ g(x) = \frac{1}{x-2} \] Now, substituting \( g(x) \) into \( f(x) \): \[ f(g(x)) = f\left( \frac{1}{x-2} \right) = \frac{5}{\frac{1}{x-2} + 2} \] To simplify the denominator: \[ \frac{1}{x-2} + 2 = \frac{1}{x-2} + \frac{2(x-2)}{x-2} = \frac{1 + 2(x-2)}{x-2} = \frac{1 + 2x - 4}{x-2} = \frac{2x - 3}{x-2} \] So now, we rewrite \( f(g(x)) \): \[ f(g(x)) = \frac{5}{\frac{2x - 3}{x-2}} = 5 \cdot \frac{x-2}{2x - 3} = \frac{5(x-2)}{2x - 3} \] Thus, we have: \[ (f \circ g)(x) = \frac{5(x-2)}{2x - 3} \] Next, we need to find the domain of \( f \circ g \). The domain of \( g(x) \) is \( x \neq 2 \) because of the denominator \( x-2 \). Additionally, for \( f(x) \), its domain excludes \( x = -2 \), but when we apply \( g \), we must check if \( g(x) = -2 \): \[ \frac{1}{x-2} = -2 \Rightarrow 1 = -2(x - 2) \Rightarrow 1 = -2x + 4 \Rightarrow 2x = 3 \Rightarrow x = \frac{3}{2} \] Thus, \( x = \frac{3}{2} \) is another restriction for the domain. So, the complete domain of \( f \circ g \) is: \[ \text{Domain of } f \circ g: x \neq 2 \text{ and } x \neq \frac{3}{2} \] Final Result: \[ \begin{array}{l}(f \circ g)(x)=\frac{5(x-2)}{2x - 3} \\ \text { Domain of } f \circ g: x \neq 2 \text{ and } x \neq \frac{3}{2} \end{array} \]

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy